CELEBRATE SUCCESS!. (March 2018) - Stanforth, Dixie; Graham, Kelsey
Abstract : Apply It!: The purpose of this article is to highlight real-world, positive change that is happening in many communities. There are numerous examples of ordinary people doing extraordinary things to shift the curve of health and fitness in a positive direction. Change is happening at all levels of the socioecological framework, from individuals to organizations, communities, and improved public policy. By reading this article the health and fitness professional will: Be inspired by the success of the three programs highlighted Be motivated to change his or her world for the better